COMPARATIVE PHYTOCHEMICAL AND PHARMACOLOGICAL SCREENING OF THE METHANOLIC EXTRACTS OF THE FRONTAL AND MATURE LEAVES OF TECTONA GRANDIS. - NAIRA NAYEEM; KARVEKAR MD (International Journal of Pharma and Bio Sciences, 2010)
The ethnopharmacological survey has revealed that only the frontal leaves of Tectona grandis have been used for the treatment of wounds. Comparative study of the activity and phytoconstituents of the mature and the frontal leaves of Tectona grandis was carried out. Wound healing activity of both the extracts was evaluated by the excision wound model. The wound healing was 100 % on the 12th day and 16th day in the frontal leaves (P<0.001) and the mature leaves (P<0.05) respectively which was quite significant. A comparative phytochemical analysis was carried out to prove that the amount of phytoconstituents varied with the stages of development of the plants which in turn may be contributing to the activity of the extract. Total phenolic acid and flavonoid content of both the extracts was estimated and was found to be more in the frontal leaf extract, giving scientific proof to the use of frontal leaves.